Interleukin 1 of the central nervous system is produced by ameboid microglia (The Rockefeller University Press, 1986)
By screening specific populations of rat brain cells, we found that ameboid microglia secrete an 18 kD peptide with IL-1 biological activity. The IL-1 activity released by microglia was found to be identical to rat macrophage IL-1 on fractionation by gel filtration and high pressure liquid anion-exchange chromatography, and it was neutralized by an antiserum specific for murine IL-1. When added to astroglia grown in culture, microglial IL-1 increased the cell number of five- to sevenfold, and increased astroglial incorporation of [3H]thymidine by three- to fivefold. We propose that the proliferation of astroglia in specific brain regions may be regulated by the signaled release of IL-1 from activated microglial cells.